2018
DOI: 10.1016/j.csr.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Tracking sea surface salinity and dissolved oxygen on a river-influenced, seasonally stratified shelf, Mississippi Bight, northern Gulf of Mexico

Abstract: River discharge, and its resulting region of freshwater influence (ROFI) in the coastal ocean, has a critical influence on physical and biogeochemical processes in seasonally stratified shelf ecosystems. Multi-year (2010-2016) observations of satellite-derived sea surface salinity (SSS) and in situ water column hydrographic data during summer 2016 were used to investigate physical aspects of the ROFI east of the Mississippi River Delta to better assess regional susceptibility to hypoxia in the summer months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The Mississippi Bight region of the northern Gulf of Mexico (nGOM) is physically complex and biologically productive due to high amounts of nutrient-laden river discharge. During the summer, highly stratified conditions are favorable for mid-water thin layer formation of marine aggregates, also known as "marine snow" (Dzwonkowski et al 2018b;Greer et al 2018a). The spatial and temporal oceanographic variability in the nGOM system is driven primarily by winds and freshwater discharge plumes (Ohlmann and Niiler 2005;Walker et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Mississippi Bight region of the northern Gulf of Mexico (nGOM) is physically complex and biologically productive due to high amounts of nutrient-laden river discharge. During the summer, highly stratified conditions are favorable for mid-water thin layer formation of marine aggregates, also known as "marine snow" (Dzwonkowski et al 2018b;Greer et al 2018a). The spatial and temporal oceanographic variability in the nGOM system is driven primarily by winds and freshwater discharge plumes (Ohlmann and Niiler 2005;Walker et al 2005).…”
mentioning
confidence: 99%
“…Despite conditions favorable for strong stratification, and the summer phenomenon of bottom-water hypoxia (dissolved O 2 < 2.0 mg L −1 , Diaz and Rosenberg 2008;Dzwonkowski et al 2018b), little is known about the ecological consequences of thin layers in the nGOM. If frequently occurring and generating overlapping high abundances among multiple trophic levels (Benoit-Bird and McManus 2012; Greer and Woodson 2016), these layers may contribute to the productive fisheries in this region (Grimes 2001).…”
mentioning
confidence: 99%
“…A growing body of work on dissolved oxygen changes in the northeast region of the Gulf of Mexico has shown that the region east of the Mississippi River Delta is susceptible to hypoxia development in the summer months (Brunner, 2006;Dzwonkowski et al, 2018;Milroy, 2016). A large focus of previous work has been on stratification and river nutrients driving low dissolved oxygen.…”
Section: Coastal Variabilitymentioning
confidence: 99%
“…The hypoxic water mass sometimes extends into upper Texas coastal waters [(maps of bottom oxygen are at https:// www.ncddc.noaa.gov/hypoxia/products/ and http://www.gulfhypoxia.net]. Hypoxia also occurs east of the Mississippi River and is becoming more frequent there (Dzwonkowski et al 2018).…”
Section: The Presentmentioning
confidence: 99%